High Performance Computing for Computational Science – VECPAR 2018 : 13th International Conference, São Pedro, Brazil, September 17-19, 2018, Revised Selected Papers /: 13th International Conference, São Pedro, Brazil, September 17-19, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available